1995
DOI: 10.1007/s00585-995-1144-2
|View full text |Cite
|
Sign up to set email alerts
|

Radar observations of auroral zone flows during a multiple-onset substorm

Abstract: Abstract. We present an analysis of ground magnetic field, ionospheric flow, geosynchronous particle, and interplanetary data during a multiple-onset substorm on 12 April 1988. Our principal results concern the modulations of the ionospheric flow which occur during the impulsive electrojet activations associated with each onset. During the first hour of the disturbance these take place every ~12.5 min and involve the formation of a new intense westward current filament in the premidnight sector, just poleward … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 0 publications
3
27
1
Order By: Relevance
“…In effect, the foci of the flow cells are shown as having been displaced toward the dayside. In common with some previous studies, therefore, we find that the flow within the high-conductivity bulge region became semi-stagnant, with the surrounding flow being diverted around it [e.g., Kirkwood et al, 1988; Morelli et al, 1995;Yeoman et al, 2000]. We note, however, that the flow in the vicinity of the Cassini footprint, which lay well to the east of the disturbed region, had also become small in this interval, a fact which will be commented upon in the next section below.…”
Section: Geophysical Conditionssupporting
confidence: 90%
“…In effect, the foci of the flow cells are shown as having been displaced toward the dayside. In common with some previous studies, therefore, we find that the flow within the high-conductivity bulge region became semi-stagnant, with the surrounding flow being diverted around it [e.g., Kirkwood et al, 1988; Morelli et al, 1995;Yeoman et al, 2000]. We note, however, that the flow in the vicinity of the Cassini footprint, which lay well to the east of the disturbed region, had also become small in this interval, a fact which will be commented upon in the next section below.…”
Section: Geophysical Conditionssupporting
confidence: 90%
“…It was shown that the location of its upward and downward current roughly coincide with the west and east terminations of the auroral bulge, respectively (e.g., Untiedt et al, 1978;Baumjohann et al, 1981;Gelpi et al, 1987;Sergeev et al, 1996). Like auroral bulge, the SCW is not a static structure; once it is formed it broadens azimuthally and radially (Nagai, 1982;Lopez and Lui, 1990;Jacquey et al, 1993;Ohtani et al, 1998). Although the sense of the SCW system for a typical substorm which initiates at the midnight-premidnight local time sector is the same as for the large-scale region 1 system, there are a few important differences.…”
Section: Substorm Current Wedge (Scw) With R1 Fac Closurementioning
confidence: 99%
“…Strong electron precipitation, such as that associated with the onset of the substorm expansion phase, ionizes the E region and enhances the ionospheric conductivity. There are several reports in the literature which suggest that the ionospheric conductivity modifies the electric field pattern and produces flow bursts [e.g., Morelli et al, 1995]. A high-conductivity region creates an obstacle which diverts the background flow around it, and the diverted flow is accelerated.…”
Section: Ionospheric Source7mentioning
confidence: 99%